Aurelio González y Beatriz Mariscal Hay (eds.), Romancero: visiones y revisiones.El Colegio de México, México, 2008; 157 pp. - Rodríguez Valle, Nieves (El Colegio de México, 2010)
Se reseña el libro:Romancero: visiones y revisiones.